Preparation method and application of mesoporous TiO2 / CNQDs-OH composite photocatalyst
Patent Information
- Application Number
- CN202510652034.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-05-20
AI Technical Summary
针对以上TiO2基光催化材料存在的问题,由于g-C3N4无毒、较窄的带隙、能带匹配、较高的光吸收系数、经济易得等优点引起了光催化领域的关注;二者因能带匹配可通过构建Ⅱ型或Z型异质结实现载流子分离效率的提高,并增强对可见光的吸收;例如专利CN116920912A,通过溶剂热法构建TiO2/g-C3N4Z型异质结有效提升了光吸收范围、光生载流子的分离效率及运输效率,从而使得其光催化分解水的效率明显提升,产氢速率可达4128μmol·g-1·h-1;该复合光催化剂虽通过2D/2D面面接触形式增强了界面相互作用,但以范德华力作为界面相互作用力仍然不利于构建稳定高效的光催化体系;同时具有多孔结构的TiO2/g-C3N4复合光催化剂虽有效增大了比表面积,增加了活性位点,但其忽视了催化剂与反应环境的相互作用,较差的亲水性使其仍需依赖贵金属pt才能实现一定的光催化活性,无疑增添了其在光催化应用的成本
[0024](1)本发明制备的介孔TiO2/CNQDs-OH复合光催化剂利用天然化合物糖类调控异质结界面作用力,通过形成化学键构建了更加稳定和高效的两相载流子传输界面,同时增强了复合光催化剂的亲水性。
Smart Images

Figure CN120586905B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing and applying a mesoporous TiO2 / CNQDs-OH composite photocatalyst, belonging to the field of nanophotocatalytic materials technology. Background Technology
[0002] Photocatalytic hydrogen evolution is a green technology that uses solar energy to split water into hydrogen and oxygen, and is considered one of the potential solutions to the energy crisis and environmental problems. With the increasing global demand for clean energy, hydrogen energy has become a research hotspot due to its high energy density and zero carbon emissions. However, traditional hydrogen production methods mainly rely on fossil fuels, which not only consume non-renewable resources but also generate large amounts of greenhouse gases. Therefore, developing efficient, green, environmentally friendly, and sustainable hydrogen production technologies has become a current research focus, and photocatalytic hydrogen evolution has emerged in this context.
[0003] Among various photocatalysts, TiO2 remains the most commonly used semiconductor in photocatalytic applications due to its low cost, easy availability, high catalytic activity, and excellent stability. However, the application of TiO2 is still limited by its relatively wide band gap, exhibiting photoresponsiveness only under ultraviolet light irradiation, and the recombination of photogenerated carriers is relatively fast. Currently, the preparation of high-performance modified TiO2 photocatalytic materials mainly includes doping modification and morphology control, such as the preparation of nanostructures and porous structures, or the doping modification of TiO2 with noble metals / non-metals, the formation of composites with low-bandgap semiconductors, and the construction of defects, which have been used to enhance visible light absorption, enhance charge separation, and extend carrier lifetime. For example, patent CN108786792A prepared a SiO2@TiO2 core-shell structure through the sol-gel method, and effectively improved the visible light absorption performance of SiO2@TiO2 / Pt-SA and its activity and stability in the photocatalytic water splitting to produce hydrogen under ultraviolet-visible light irradiation by optimizing the spatial distribution of Pt nanoparticles on the SiO2@TiO2 surface, achieving a hydrogen production rate of 2.6 mmol·g. -1 ·h -1 However, this heterojunction relies on the noble metal Pt to provide active sites and improve the separation efficiency of photogenerated carriers. The limited number of active sites significantly increases the cost of its application in photocatalytic water splitting. Furthermore, the thickness of the TiO2 shell is difficult to control, which greatly affects the migration rate and separation efficiency of photogenerated carriers. For example, CN116832839A uses a simple hydrothermal method followed by heat treatment to obtain a 2D Ni2P photocatalyst, which is then composited with simple stirring to obtain a 2DNi2P / TiO2 composite material. This composite photocatalyst effectively improves the photoinduced carrier separation efficiency and interfacial charge transfer transition due to the larger contact area of the 2D / 2D structures, the faster electron transport of 2D Ni2P, and the shorter transport distance. However, its optimal photocatalytic efficiency is only 894.2 μmol·g⁻¹. -1 ·h-1 Furthermore, the heterojunction interface forces formed by simple loading are relatively weak, and the resulting heterojunction is prone to detachment, which still limits the rapid migration of photogenerated carriers and the stability of composite photocatalysts.
[0004] Therefore, the light absorption and conversion efficiency of TiO2-based photocatalysts remains limited, and problems such as low specific surface area, few active sites, dependence on noble metal co-catalysts, and weak interfacial interactions in composite photocatalysis persist. To address these issues, g-C3N4 has attracted attention in the photocatalysis field due to its advantages such as non-toxicity, narrow band gap, band matching, high light absorption coefficient, and economic availability. The band matching between the two materials allows for the construction of type II or Z-type heterojunctions to improve carrier separation efficiency and enhance visible light absorption. For example, patent CN116920912A demonstrates how a solvothermal method for constructing a TiO2 / g-C3N4 Z-type heterojunction effectively improves the light absorption range, photogenerated carrier separation efficiency, and transport efficiency, thereby significantly enhancing its photocatalytic water splitting efficiency, achieving a hydrogen production rate of 4128 μmol·g⁻¹. -1 ·h -1 Although this composite photocatalyst enhances interfacial interactions through 2D / 2D face-to-face contact, relying on van der Waals forces as the interfacial interaction force is still not conducive to constructing a stable and efficient photocatalytic system. Meanwhile, while the porous TiO2 / g-C3N4 composite photocatalyst effectively increases the specific surface area and active sites, it neglects the interaction between the catalyst and the reaction environment. Its poor hydrophilicity means it still relies on the noble metal Pt to achieve a certain level of photocatalytic activity, undoubtedly increasing its cost in photocatalytic applications. This also limits the application of g-C3N4 modified TiO2 composite materials in the field of photocatalysis.
[0005] Therefore, optimizing the interface structure of the modified g-C3N4 and TiO2 heterojunction and the interaction between the catalyst and the reaction environment to achieve a photocatalytic system with high specific surface area, high hydrophilicity, strong interfacial forces, and high carrier transfer and separation efficiency without relying on precious metals has become an urgent scientific problem to be solved in the field of photocatalysis. Summary of the Invention
[0006] To address or partially address the problems existing in related technologies, one objective of this invention is to provide a method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst, the main steps of which are as follows:
[0007] (1) After mixing polyoxyethylene polyoxypropylene ether (F127), tetrahydrofuran (THF), acetic acid (AcOH), and hydrochloric acid (HCl) to form a transparent solution, tetrabutyl titanate (TBOT) is added and stirred until a golden-yellow completely homogeneous solution is formed.
[0008] (2) The completely homogenized solution was dried at low temperature to obtain F127 / TiO2 hydrogel.
[0009] (3) Dry the F127 / TiO2 hydrogel at high temperature and collect the powder.
[0010] (4) The powder obtained in step (4) is subjected to heat preservation treatment to obtain mesoporous TiO2.
[0011] (5) Mix the carbon nitride precursor with hydroxyl-rich sugars to form a solid mixture.
[0012] (6) The solid mixture obtained in step (5) is mixed evenly with the mesoporous TiO2 obtained in step (4) and then calcined to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0013] Preferably, in step (1), the mass-to-volume ratio of polyoxyethylene polyoxypropylene ether to tetrahydrofuran is 4:(20-28), in g:mL; the mass ratio of polyoxyethylene polyoxypropylene ether to tetrabutyl titanate is 8:(15-25); and the volume ratio of tetrahydrofuran, acetic acid and hydrochloric acid is 100:(20-25):(10-20).
[0014] Preferably, the temperature for low-temperature drying in step (2) is 40–50°C.
[0015] Preferably, the high-temperature drying temperature in step (3) is 70-85°C.
[0016] Preferably, the heat preservation conditions in step (4) are: heating to 350-450°C at a heating rate of 1°C / min and maintaining the temperature for 2-4 hours.
[0017] Preferably, in step (5), the mass ratio of carbon nitride precursor to hydroxyl-rich sugar is 20000:(1-8).
[0018] Preferably, the carbon nitride precursor in step (5) is either urea or melamine; and the hydroxyl-rich sugar is either sucrose, fructose, glucose or maltose.
[0019] Preferably, in step (6), the mass ratio of the solid mixture to mesoporous TiO2 is (5-80):1.
[0020] Preferably, the firing conditions in step (6) are: heating at a rate of 10℃ / min to 500-620℃, and holding at that temperature for 2-4 hours.
[0021] The second objective of this invention is to provide a mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0022] The third objective of this invention is to apply the prepared mesoporous TiO2 / CNQDs-OH composite photocatalyst in photocatalytic water splitting for hydrogen production.
[0023] The technical solution provided by this invention may include the following beneficial effects:
[0024] (1) The mesoporous TiO2 / CNQDs-OH composite photocatalyst prepared in this invention utilizes natural compound sugars to regulate the interface forces of the heterojunction, and constructs a more stable and efficient two-phase carrier transport interface by forming chemical bonds, while enhancing the hydrophilicity of the composite photocatalyst.
[0025] (2) The mesoporous TiO2 / CNQDs-OH composite photocatalyst synthesized in this invention has a high specific surface area and a mesoporous structure that can provide more active sites. The synergistic effect of the mesoporous structure and strong interfacial forces can realize the rapid migration of multi-channel charge carriers, which greatly promotes the separation and transport of photogenerated charges, and is conducive to achieving stronger photoresponse capability and higher photocatalytic water splitting hydrogen production efficiency.
[0026] (3) Furthermore, the mesoporous TiO2 / CNQDs-OH composite photocatalyst does not rely on noble metals (Pt, Rh, etc.) as co-catalysts in practical applications and still exhibits good photocatalytic performance. It is also lower in cost, more environmentally friendly, and has a simpler process, which meets the actual production needs and is conducive to large-scale promotion. Attached Figure Description
[0027] Figure 1 This is a process flow diagram of the mesoporous TiO2 / CNQDs-OH composite photocatalyst of the present invention.
[0028] Figure 2 The images show (a) a TEM transmission electron microscope image and (b) an EDX spectrum of the mesoporous TiO2 / CNQDs-OH composite photocatalyst obtained in Example 1.
[0029] Figure 3 The figures show (a) nitrogen adsorption-desorption curves and (b) Barret-Joyner–Halenda (BJH) pore size analysis diagrams of the mesoporous TiO2 and mesoporous TiO2 / CNQDs-OH composite photocatalysts obtained in Example 1.
[0030] Figure 4 The images show the FT-IR Fourier transform infrared spectra of the mesoporous TiO2, the mesoporous TiO2 / CNQDs-OH composite photocatalyst obtained in Example 1, and the mesoporous TiO2 / CNQDs obtained in Comparative Example 2.
[0031] Figure 5The images show the XRD patterns of the mesoporous TiO2, the mesoporous TiO2 / CNQDs-OH composite photocatalyst obtained in Example 1, and the CNQDs-OH obtained in Comparative Example 3.
[0032] Figure 6 This is a comparison chart of the photocatalytic water splitting and hydrogen production activities of the mesoporous TiO2 / CNQDs-OH composite photocatalyst obtained in Example 1, the mesoporous TiO2-580 obtained in Comparative Example 1, and the mesoporous TiO2 / CNQDs obtained in Comparative Example 2. Detailed Implementation
[0033] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited to the content described.
[0034] Unless otherwise specified, all reagents used are commercially available analytical grade reagents.
[0035] Example 1
[0036] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst, the process flow is as follows: Figure 1 As shown, it includes the following steps:
[0037] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0038] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0039] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0040] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0041] (5) Grind 20g of urea and 2mg of sucrose evenly and record it as a solid mixture.
[0042] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at this temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0043] The mesoporous TiO2 / CNQDs-OH composite photocatalyst prepared in Example 1 was analyzed by TEM transmission electron microscopy and EDX energy dispersive spectroscopy. Figure 2 As shown. By Figure 2 TEM revealed that after calcination with urea, the surface of the mesoporous TiO2 was exposed with many g-C3N4 nanodots (CNQDs). Combined with EDX energy dispersive spectroscopy analysis, the uniform distribution of the characteristic elements titanium (Ti), oxygen (O), carbon (C), and nitrogen (N) of the composite photocatalyst was observed, indicating the uniform distribution of CNQDs on the mesoporous TiO2 and the successful preparation of the composite photocatalyst.
[0044] Nitrogen adsorption-desorption experiments and Barret-Joyner–Halenda (BJH) pore size analysis were performed on the mesoporous TiO2 and mesoporous TiO2 / CNQDs-OH composite photocatalyst obtained in Example 1. The results are as follows: Figure 3 As shown in Table 1, both the obtained mesoporous TiO2 and mesoporous TiO2 / CNQDs-OH exhibit typical type IV isotherms, and their pore size distribution curves are centered at 13.99 and 16.76 nm, respectively. This indicates that both have a uniform and well-defined mesoporous structure. The attachment of CNQDs-OH did not disrupt the mesoporous structure of the mesoporous TiO2, which provides more active sites and facilitates multi-channel transport of charge carriers. However, after loading CNQDs-OH, its specific surface area (S) decreased. BJH The value decreased from 86.87 to 45.24m. 2 / g, pore volume (V) BJH The value decreased from 0.38 to 0.29 cm. 3 / g, this is because the high specific surface area of mesoporous TiO2 is conducive to the adhesion of more CNQDs-OH, and CNQDs-OH will adhere to its surface and mesoporous structure, thereby reducing its specific surface area to a certain extent.
[0045] Table 1. Specific surface area, pore volume, and average pore size of photocatalysis.
[0046] <![CDATA[Mesoporous TiO2]]> 86.87 0.38 13.99 <![CDATA[Mesoporous TiO2 / CNQDs-OH]]> 45.24 0.29 16.76
[0047] according to Figure 4 The FT-IR plots show that pure mesoporous TiO2 has three main absorption regions, with the largest being 3458 cm⁻¹. -1 The broad peak centered at 1630 cm⁻¹ is attributed to the OH stretching vibration of physically adsorbed water on the TiO₂ surface. -1 The relatively sharp absorption peak at 850 cm⁻¹ corresponds to the bending vibration of the OH group in water molecules. -1The strong absorption observed below belongs to Ti-O absorption; while the absorption peaks of mesoporous TiO2 / CNQDs-OH are similar to those of mesoporous TiO2, but at 1310 and 1123 cm⁻¹. -1 Two additional absorption peaks were observed, originating from the stretching vibrations of the CN heterocycle and CO, respectively. These results provide direct evidence of the successful preparation of the mesoporous TiO2 / CNQDs-OH heterojunction and the formation of hydroxyl groups at the edge positions of the CNQDs. Furthermore, the OH absorption peaks of the mesoporous TiO2 / CNQDs-OH showed a red shift and were stronger compared to those of the mesoporous TiO2, indicating that the hydroxylated CNQDs formed hydrogen bonds with the mesoporous TiO2, which not only effectively enhanced the interfacial forces and hydrophilicity, but also facilitated the formation of bridging oxygen bonds at the interface due to the presence of hydroxyl-rich surfaces, further enhancing the interfacial forces.
[0048] according to Figure 5 The XRD patterns show that the diffraction peaks of the mesoporous TiO2 prepared in Example 1 are consistent with the characteristic diffraction peaks of pure TiO2 (PDF#21-1272), indicating that its crystal form is anatase phase. The diffraction peaks of the mesoporous TiO2 / CNQDs-OH prepared in Example 1 are consistent with the characteristic diffraction peaks of pure TiO2 (PDF#21-1272) and also with the characteristic diffraction peaks of pure TiO2 (PDF#21-1276), indicating that the crystal structure of the composite photocatalyst prepared at 580℃ has changed, and part of the anatase phase has transformed into the rutile phase.
[0049] Example 2
[0050] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0051] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 8mL of THF, and then 1.6mL of AcOH solution and 0.8mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then 3g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0052] (2) The completely homogenized solution was dried in an oven at 40°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0053] (3) The F127 / TiO2 hydrogel was placed in an oven at 70℃ for 15 hours and the powder was collected.
[0054] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 350°C at a heating rate of 1°C / min for 2 hours. After cooling to room temperature, mesoporous TiO2 is obtained.
[0055] (5) Grind 20g of urea and 2mg of sucrose evenly and record it as a solid mixture.
[0056] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at this temperature for 2h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0057] Example 3
[0058] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0059] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 11.2mL of THF, and then 2.8mL of AcOH solution and 2.24mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then 5g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0060] (2) The completely homogenized solution was dried in an oven at 50°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0061] (3) The F127 / TiO2 hydrogel was placed in an oven at 85℃ for 15 hours and the powder was collected.
[0062] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 450°C at a heating rate of 1°C / min for 4 hours. After cooling to room temperature, mesoporous TiO2 is obtained.
[0063] (5) Grind 20g of urea and 2mg of sucrose evenly and record it as a solid mixture.
[0064] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at this temperature for 4h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0065] Example 4
[0066] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0067] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0068] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0069] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0070] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0071] (5) Grind 20g of melamine and 2mg of sucrose evenly and record it as a solid mixture.
[0072] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at this temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0073] Example 5
[0074] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0075] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0076] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0077] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0078] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0079] (5) Grind 20g of urea and 2mg of fructose evenly and record it as a solid mixture.
[0080] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at this temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0081] Example 6
[0082] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0083] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0084] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0085] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0086] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0087] (5) Grind 20g of urea and 2mg of glucose evenly and record it as a solid mixture.
[0088] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at this temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0089] Example 7
[0090] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0091] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0092] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0093] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0094] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0095] (5) Grind 20g of urea and 2mg of maltose evenly and record it as a solid mixture.
[0096] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at this temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0097] Example 8
[0098] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0099] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0100] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0101] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0102] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0103] (5) Grind 20g of urea and 1mg of sucrose evenly and record it as a solid mixture.
[0104] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at this temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0105] Example 9
[0106] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0107] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0108] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0109] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0110] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0111] (5) Grind 20g of urea and 4mg of sucrose evenly and record it as a solid mixture.
[0112] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at this temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0113] Example 10
[0114] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0115] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0116] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0117] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0118] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0119] (5) Grind 20g of urea and 8mg of sucrose evenly to obtain a solid mixture.
[0120] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at this temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0121] Example 11
[0122] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0123] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0124] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0125] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0126] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0127] (5) Grind 20g of urea and 2mg of sucrose evenly and record it as a solid mixture.
[0128] (6) Take 50mg of mesoporous TiO2 and 0.25g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at that temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0129] Example 12
[0130] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0131] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0132] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0133] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0134] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0135] (5) Grind 20g of urea and 2mg of sucrose evenly and record it as a solid mixture.
[0136] (6) Take 50mg of mesoporous TiO2 and 1g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at that temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0137] Example 13
[0138] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0139] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0140] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0141] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0142] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0143] (5) Grind 20g of urea and 2mg of sucrose evenly and record it as a solid mixture.
[0144] (6) Take 50mg of mesoporous TiO2 and 2g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at that temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0145] Example 14
[0146] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0147] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0148] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0149] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0150] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0151] (5) Grind 20g of urea and 2mg of sucrose evenly and record it as a solid mixture.
[0152] (6) Take 50mg of mesoporous TiO2 and 4g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding it at that temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0153] Example 15
[0154] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0155] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0156] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0157] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0158] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0159] (5) Grind 20g of urea and 2mg of sucrose evenly and record it as a solid mixture.
[0160] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 500℃ at a heating rate of 10℃ / min. After holding it at that temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0161] Example 16
[0162] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0163] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0164] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0165] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0166] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0167] (5) Grind 20g of urea and 2mg of sucrose evenly and record it as a solid mixture.
[0168] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 540℃ at a heating rate of 10℃ / min. After holding it at that temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0169] Example 17
[0170] A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst includes the following steps:
[0171] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. Then, 3.4g of TBOT was quickly added and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0172] (2) The completely homogenized solution was dried in an oven at 45°C for 24 hours to obtain F127 / TiO2 hydrogel.
[0173] (3) The F127 / TiO2 hydrogel was placed in an oven at 80℃ for 15 hours and the powder was collected.
[0174] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0175] (5) Grind 20g of urea and 2mg of sucrose evenly and record it as a solid mixture.
[0176] (6) Take 50mg of mesoporous TiO2 and 0.5g of solid mixture, grind them evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 620℃ at a heating rate of 10℃ / min. After holding it at this temperature for 3h, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0177] The properties of the mesoporous TiO2 / CNQDs-OH composite photocatalysts prepared in Examples 2 to 17 are similar to those in Example 1.
[0178] Comparative Example 1
[0179] A method for preparing a mesoporous TiO2-580 photocatalyst includes the following steps:
[0180] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent solution. 3.4g of TBOT was quickly added to the solution and stirred for 30min to form a golden-yellow completely homogeneous solution.
[0181] (3) Dry the solution in an oven at 45°C for 24 hours, then place it in an oven at 80°C for 15 hours and collect the powder.
[0182] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0183] (5) 50 mg of mesoporous TiO2 was ground and transferred to a covered alumina crucible, and then placed in a tube furnace and heated to 580 °C at a heating rate of 10 °C / min. After holding at the temperature for 3 h, it was cooled to room temperature to obtain mesoporous TiO2-580 photocatalyst.
[0184] Comparative Example 2
[0185] A method for preparing a mesoporous TiO2 / CNQDs composite photocatalyst includes the following steps:
[0186] (1) Under mechanical stirring, 1.6g of F127 was added to a container containing 10mL of THF, and then 2.4mL of AcOH solution and 1.5mL of HCl solution were added dropwise. The mixture was stirred to form a transparent and completely homogeneous solution. 3.4g of TBOT was quickly added to the solution and stirred for 30min to form a golden and completely homogeneous solution.
[0187] (3) The completely homogenized solution was first dried in an oven at 45°C for 24 hours, and then placed in an oven at 80°C for 15 hours to collect the powder.
[0188] (4) Transfer the powder to a covered alumina crucible, place it in a muffle furnace and heat it to 400℃ at a heating rate of 1℃ / min for 3h. After cooling to room temperature, mesoporous TiO2 is obtained.
[0189] (5) Grind 0.5g of urea and 50mg of mesoporous TiO2 evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 580℃ at a heating rate of 10℃ / min. After holding at this temperature for 3 hours, cool it to room temperature to obtain the mesoporous TiO2 / CNQDs composite photocatalyst. The FT-IR Fourier transform infrared spectrum is shown below. Figure 4 As shown.
[0190] Comparative analysis of the FT-IR spectra of the mesoporous TiO2 / CNQDs-OH composite photocatalyst prepared in Example 1 and the mesoporous TiO2 / CNQDs composite photocatalyst prepared in Comparative Example 2 shows that their absorption peaks are similar, indicating the formation of heterojunctions, except that the latter lacks the peak at 1123 cm⁻¹. -1 The presence of CO absorption peaks indicates that the addition of hydroxyl-rich glycogen successfully achieved hydroxylation at the edge of CNQDs. Furthermore, the OH peak of mesoporous TiO2 / CNQDs-OH exhibits a more significant red shift compared to mesoporous TiO2 / CNQDs, suggesting that hydroxylation of CNQDs further strengthens interfacial interactions, facilitating the migration and separation of photogenerated carriers and improving the stability of the mesoporous TiO2 / CNQDs-OH composite photocatalyst.
[0191] Comparative Example 3
[0192] A method for preparing a CNQDs-OH composite photocatalyst includes the following steps:
[0193] (1) Grind 20g of urea and 2mg of sucrose evenly and transfer them to a covered alumina crucible. Then place it in a tube furnace and heat it to 500℃ at a heating rate of 10℃ / min. After holding at this temperature for 3 hours, cool it to room temperature to obtain the CNQDs-OH photocatalyst. The XRD pattern is shown below. Figure 5 As shown.
[0194] according to Figure 5 XRD analysis showed that CNQDs-OH prepared in Comparative Example 3 had characteristic diffraction peaks consistent with pure g-C3N4, corresponding to the (002) crystal plane, indicating that g-C3N4 was successfully prepared and that the doping of sucrose did not cause the diffraction peaks to shift.
[0195] Example of effect
[0196] The hydrogen production performance of the mesoporous TiO2 / CNQDs-OH composite photocatalyst prepared in Example 1, the mesoporous TiO2-580 photocatalyst prepared in Comparative Example 1, and the mesoporous TiO2 / CNQDs prepared in Comparative Example 2 was studied. The process is as follows:
[0197] Using a xenon lamp as the hydrogen production light source with a wavelength range of ≥320 nm, a catalyst dosage of 1.5 g / L, 20 mL of triethanolamine as the sacrificial agent, and 60 mL of water, the reaction cell was evacuated. Argon was used as the carrier gas, and the generated H2 was detected using gas chromatography. A 4-hour hydrogen production experiment was conducted, with hydrogen data collected every hour. The photocatalytic hydrogen production effects of the mesoporous TiO2 / CNQDs-OH obtained in Example 1, the mesoporous TiO2-580 prepared in Comparative Example 1, and the mesoporous TiO2 / CNQDs photocatalyst prepared in Comparative Example 2 under a xenon lamp are shown in the figure. Figure 6 As shown, the horizontal axis represents time, the vertical axis represents hydrogen production, and the upper curve is the curve of hydrogen production of the sample obtained by the method of this invention under a xenon lamp with triethanolamine as a sacrificial agent as a function of time.
[0198] according to Figure 6 Comparative analysis revealed that the mesoporous TiO2 / CNQDs-OH composite photocatalyst achieved a hydrogen production rate of 2382 μmol·g within 4 hours. -1 ·h -1 The hydrogen production rate is significantly higher than that of the mesoporous TiO2-580 photocatalyst (313 μmol·g⁻¹). -1 ·h -1 The hydrogen production rate of the mesoporous TiO2 / CNQDs composite photocatalyst (292 μmol·g) was [not specified]. -1 ·h -1 This indicates that the enhanced photocatalytic activity of the composite photocatalyst prepared in this invention is due to the enhanced interaction between the two-phase interfaces modified with hydroxyl-rich sugars and the effective improvement of the hydrophilicity of the catalytic system.
[0199] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or improvement of the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. A method for preparing a mesoporous TiO2 / CNQDs-OH composite photocatalyst, characterized in that: The main steps are as follows: (1) After mixing polyoxyethylene polyoxypropylene ether, tetrahydrofuran, acetic acid and hydrochloric acid to form a transparent solution, tetrabutyl titanate is added and stirred evenly to form a golden yellow completely homogeneous solution. (2) The completely homogenized solution was dried at low temperature to obtain F127 / TiO2 hydrogel; (3) Dry the F127 / TiO2 hydrogel at high temperature and collect the powder; (4) The powder obtained in step (3) is subjected to heat preservation treatment to obtain mesoporous TiO2; (5) Mix the carbon nitride precursor with hydroxyl-rich sugars to form a solid mixture; (6) The solid mixture obtained in step (5) is mixed evenly with the mesoporous TiO2 obtained in step (4) and then calcined to obtain the mesoporous TiO2 / CNQDs-OH composite photocatalyst; The mass ratio of the solid mixture to mesoporous TiO2 is (5-80):1; the firing temperature is 500-620℃.
2. The preparation method of the mesoporous TiO2 / CNQDs-OH composite photocatalyst according to claim 1, characterized in that: In step (1), the mass-to-volume ratio of polyoxyethylene polyoxypropylene ether to tetrahydrofuran is 4:(20-28), in g:mL; the mass ratio of polyoxyethylene polyoxypropylene ether to tetrabutyl titanate is 8:(15-25); and the volume ratio of tetrahydrofuran, acetic acid and hydrochloric acid is 100:(20-25):(10-20).
3. The preparation method of the mesoporous TiO2 / CNQDs-OH composite photocatalyst according to claim 1, characterized in that: The temperature for low-temperature drying in step (2) is 40-50℃.
4. The preparation method of the mesoporous TiO2 / CNQDs-OH composite photocatalyst according to claim 1, characterized in that: The high-temperature drying temperature in step (3) is 70-85℃.
5. The preparation method of the mesoporous TiO2 / CNQDs-OH composite photocatalyst according to claim 1, characterized in that: The heat preservation conditions in step (4) are: heating to 350-450℃ at a heating rate of 1℃ / min and maintaining the temperature for 2-4 hours.
6. The preparation method of the mesoporous TiO2 / CNQDs-OH composite photocatalyst according to claim 1, characterized in that: In step (5), the mass ratio of carbon nitride precursor to hydroxyl-rich sugar is 20000:(1-8).
7. The preparation method of the mesoporous TiO2 / CNQDs-OH composite photocatalyst according to claim 1, characterized in that: The carbon nitride precursor in step (5) is either urea or melamine; the hydroxyl-rich sugar is either sucrose, fructose, glucose or maltose.
8. The method for preparing the mesoporous TiO2 / CNQDs-OH composite photocatalyst according to claim 1, characterized in that: The firing conditions in step (6) are: heating rate of 10℃ / min and holding time of 2 to 4 hours.
9. The mesoporous TiO2 / CNQDs-OH composite photocatalyst is prepared by the preparation method according to any one of claims 1 to 8.
10. The application of the mesoporous TiO2 / CNQDs-OH composite photocatalyst prepared by the preparation method according to any one of claims 1 to 8 in photocatalytic water splitting for hydrogen production.
Citation Information
Patent Citations
Metal / semiconductor composite photocatalyst and preparation and application thereof
CN108786792A
Preparation method of two-dimensional nickel phosphide / titanium dioxide photocatalytic hydrogen production material
CN116832839A
Mesoporous P25 titanium dioxide microspheres and preparation method thereof
CN107117649A
Preparation method of hydrophilic conjugated polymer composite hydroxyl-rich carbon nitride photocatalyst
CN117563664A